Hungarian Monitoring, 15 November 1990 . [Magyar rádiófigyelő], 1990. november 15 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - European Gypsy Parliament formed - Ethnic tensions in Yugoslavia - US reservists called up -100% inflation possible in the Soviet Union - Chancellor Kohl on support for Eastern European economies - More demonstrations in Bucharest - Former Czechoslovak foreign minister taken into custody Domestic Affairs: - Hungarian-South Korean discussions - István Csurka's arguments for the press law - Gábor Demszky's first consulting hour as Budapest mayor - Hungarian Inventors' Association wins ministerial special prize at Brussels World Exposition Economy: - 10% of state property could end up in workers' hands - MNH raises central bank basic interest rates - Conference on pre-privatization - Problems with children's diets Külpolitika: - Megalakult az Európai Cigányság Parlamentje - Etnikai feszültségek Jugoszláviában - Tartalékosok behívása az Egyesült Államokban - 100%-os infláció is lehetséges a Szovjetunióban - Kohl kancellár a kelet-európai gazdaságok támogatásáért - Újabb tüntetések Bukarestben - Őrizetbe veszik a volt csehszlovák külügyminisztert Belpolitika: - Magyar-dél - Koreai tárgyalások - Csurka István érvei a sajtótörvény mellett - Demszky Gábor első főpolgármesteri fogadóórája - Miniszteri különdíjat kapott a Magyar Feltalálók Egyesülete a brüsszeli világkiállításon Gazdaság: - Az állami tulajdon 10%-a kerülhet a dolgozók tulajdonába - Az MNB megemelte a jegybanki alapkamatokat - Konferencia az előprivatizációról - Problémák a gyermekétkeztetésben